Effective Carbon Dioxide Photoreduction over Metals (Fe-, Co-, Ni-, and Cu-) Incorporated TiO2/Basalt Fiber Films - Jeong Yeon Do; Byeong Sub Kwak; Sun-Min Park; Misook Kang (International Journal of Photoenergy)
Mineralogical basalt fibers as a complementary adsorbent were introduced to improve the adsorption of CO2 over the surfaces of photocatalysts. TiO2 photocatalysts (M-TiO2) incorporated with 5.0 mol.% 3d-transition metals (Fe, Co, Ni, and Cu) were prepared using a solvothermal method and mixed with basalt fibers for applications to CO2 photoreduction. The resulting 5.0 mol.% M-TiO2 powders were characterized by X-ray diffraction, scanning electron microscopy, ultraviolet-visible spectroscopy, photoluminescence, Brunauer, Emmett, and Teller surface area, and CO2-temperature-programmed desorption. A paste composed of two materials was coated and fixed on a Pyrex plate by a thermal treatment. The 5.0 mol.% M-TiO2/basalt fiber films increased the adsorption of CO2 significantly, indicating superior photocatalytic behavior compared to pure TiO2 and basalt fiber films, and produced 158~360 μmol gcat-1 L−1 CH4 gases after an 8 h reaction. In particular, the best performance was observed over the 5.0 mol.% Co-TiO2/basalt fiber film. These results were attributed to the effective CO2 gas adsorption and inhibition of photogenerated electron-hole pair recombination.